Bronkopneumonia pada Bayi Usia 5 Bulan dengan Klinis Sindrom Down dan Suspek Hipotiroid Kongenital - Febriy Firizki S; Elvi Suryati (MAJORITY, 2020)
A baby boy, 5 months old with complaints shortness of breath since 2 days was getting heavier over time. Previously, the patient had a persistent fever since 5 days. The patient also had a cough with phlegm since 4 days. Physical examination revealed compos mentis awareness; temperature 38.5 0C; pulse 128x / minute, breathing 64x / minute; weight 5.1 kg, good nutritional status. The occiput head is flat, the face is dysmorphic; the eye shows bilateral medial epicanthic folds, upward oblique palpebral fissures. The ears are small and low lying, the nose is small, the nasal bridge is flat, the nostrils breath, the tongue macroglossia. The chest examination showed suprasternal and substernal retraction and additional breath sounds could be heard soft wet crackles. The abdomen shows an umbilical hernia. The superior extremities show short and wide hands, simian crease, clinodactyly at 5th finger, hypotonia. The inferior limb shows a wide gap of the 1st and 2nd toes, hypotonia. Routine blood laboratory tests showed 13000 / μl leukocytes and a diff.count value of 0/0/0 /45/49/6. Two times the chest X-rays showed bronchopneumonia results. This patient was diagnosed bronchopneumonia with Down's syndrome clinic and suspected congenital hypothyroidism.